EVALUATION OF THE PHYTOCHEMICAL PROPERTIES AND DNA PROTECTIVE ACTIVITY OF BOLANTHUS ORTEGIOIDES (FISCH. and C.A. MEY.) MADHANI and RABELER - Görkem Deniz Sönmez (Journal of Animal and Plant Sciences, 2023)
The aim of this study was to elucidate the potential of the flora of Turkey by investigating the phytochemical properties of the endemic plant species Bolanthus ortegioides of the family Caryophyllaceae. The identity of the plant was validated through a phylogenetic approach with DNA barcoding using the internal transcribed spacer [ITS] region. Methanolic extract of B. ortegioides was examined by HPLC, and the total phenolic content was measured. In addition, pBluescript II SK(+) plasmid DNA cleavage was induced by ultraviolet (UV) photolysis of hydrogen peroxide (H2O2), and the activity of the methanolic extract of B. ortegioides against oxidative DNA damage was examined. The total phenolic content of the extract was 5.6 ± 0.25 µg (gallic acid equivalent [GAE])/mg. Of 15 phenolic compounds analysed by HPLC, vanillic acid was found to be a major compound. Chlorogenic, caffeic, epicatechin, p-coumaric, ferulic, rutin and chicoric acids were also detected. The results showed that B. ortegioides methanolic extract offered moderate protection against DNA damage.
Keywords: Phenolic content; methanolic extract; DNA cleavage; Caryophyllaceae; phytochemistry